A Novel Reactivity of Phosphanylalumane (>P−Al<): Reversible Addition of a Saturated Interelement Bond to Olefins. Issue 44 (5th July 2021) - Yanagisawa, Tatsuya; Mizuhata, Yoshiyuki; Tokitoh, Norihiro
Abstract: The reversible addition of olefins to a phosphanylalumane, P−Al single‐bond species, was investigated. The P−Al bond added to ethylene and relatively small terminal alkenes (propylene and hex‐1‐ene) at room temperature to give the corresponding alkene adducts. Heating the terminal alkene adducts released the corresponding alkenes and regenerated the P−Al bond, but no release of ethylene was observed even under vacuum conditions. The reactivity of ethylene adduct as a new saturated C2 vicinal P/Al‐based FLP was also investigated. The ethylene adduct was found to undergo complexation with nitriles to give the corresponding nitrile adducts to the Al center, which retained the ethylene tether as in the case of the corresponding P/B‐based FLP. However, the reactivity of ethylene toward CO2 and benzaldehyde differed from that of the P/B system giving the corresponding adducts. Abstract : Keen on alkenes : Phosphanylalumane (P−Al single‐bond compound) was treated with relatively small terminal olefins (ethylene, propylene, and hex‐1‐ene) at room temperature. Heating of propylene‐ and hex‐1‐ene adducts regenerated the P−Al bond with liberation of the corresponding olefins. An unprecedented reactivity of the ethylene adduct with the release of ethylene was demonstrated, in sharp contrast to the conventional P/B system.